Подождите немного. Документ загружается.
x
c
r
c
P
T
(t) δ(t)
s(t) E
q
(t) h(t) q(t)
U (t)
P (t)
U
1
(t) U
2
(t)
M(t)=M
0
= const
y
12
=0
y
12
=0
x
c
r
c
x
d
r
x
c
r
c
x
c
(t) r
c
(t)
U
1
= U
APB
U
2
= µ
PT
K
∆U
= 150 K
1U
=7 K
∆ω
=30 K
1ω
=8 ∆
1
=∆ω K
2
1
=0
k =0, 4 σ =0, 05
x
c
(t) r
c
(t)
x
c
= r
c
=0
U
c
=0 x
c
r
c
U
c
=1
P = E
q
U
c
y
12
y
12
=0
∆t
y
11
= y
12
=0; α
11
= α
12
=0 t
0
<t<t
0
+∆t.
t
0
=10
∆t =0, 4 ∆t>0, 4
∆t =0, 9
s(t) U (t)
s(t) U (t)
P (t)
s(t) U (t)
ψ
s
=0,s = 1,m
•
•
•
•
S
PS
:
dδ
i
dt
= s
i
;
ds
i
dt
= b
1i
(P
Ti
− E
2
qi
y
ii
sin(α
ii
) − E
qi
E
qj
y
ij
sin(δ
i
− δ
j
− α
ij
) − w
i
);
dw
i
dt
= ξ
i
s
i
;
S
SG
:
dE
qi
dt
= b
2i
(−E
qi
+ b
3i
s
i
sin(δ
i
− α
ij
)+U
1i
);
S
T
:
dP
Ti
dt
= b
4i
(−P
Ti
+ q
i
C
i
);
dq
i
dt
= b
6i
(−γ
i
(q
i
) − b
5i
s
i
+ h
i
);
dh
i
dt
= b
7i
(−h
i
+ U
2i
),
i = 1, 2,j = i S
PS
S
SG
S
T
U
1i
U
2i
U
0i
− U =0,
U
0i
i
P
0
Ti
− P
Ti
=0,
P
0
Ti
i
ψ
1i
= U
2
0i
− U
2
i
= U
2
0i
− (E
2
qi
A
i
+2B
i
(δ
i
)E
qi
+ D
i
),
ψ
2i
= h
i
− ϕ
1i
(P
Ti
,q
i
,s
i
),
T
1i
˙
ψ
1i
(t)+ψ
1i
=0,
T
2i
˙
ψ
2i
(t)+ψ
2i
=0.
i =1, 2
U
1i
U
1i
= E
qi
− b
3i
s
i
sin(δ
i
− α
ij
) −
∂ψ
1i
∂δ
i
s
i
+
1
T
1i
ψ
1i
∂ψ
1i
∂E
qi
b
2i
,
∂ψ
1i
∂δ
i
= −2E
qi
∂B
i
(δ
i
)
∂δ
i
=2E
qi
U
c
y
ij
x
di
(sin(δ
i
−α
ij
)−y
ii
x
di
sin(δ
i
−α
ij
+α
ii
))
∂ψ
1i
∂E
qi
= −2A
i
E
qi
−
2B
i
(δ
i
)
ψ
1i
=0 ψ
2i
=0
T
1i
> 0 T
2i
> 0 ψ
1i
=0 ψ
2i
=0
ψ
1i
=0 ψ
2i
=0
h
i
E
qi
ψ
2i
=0
dP
Ti
dt
= b
4i
(−P
Ti
+ q
i
C
i
);
dq
i
dt
= b
6i
(−γ
i
(q
i
) − b
5i
s
i
+ ϕ
1i
(P
Ti
,q
i
,s
i
)).
ϕ
1i
(P
Ti
,q
i
,s
i
)
ψ
3i
= q
i
− ϕ
2i
(P
Ti
),
T
3i
˙
ψ
3i
(t)+ψ
3i
=0.
T
3i
> 0
ψ
3i
=0
q
i
= ϕ
2i
(P
Ti
)
ψ
3i
=0
dP
Ti
dt
= b
4i
−P
Ti
+ C
i
ϕ
2i
(P
Ti
)
.
ϕ
2i
(P
Ti
)
ψ
4i
= P
0
Ti
− P
Ti
,
T
4i
˙
ψ
4i
(t)+ψ
4i
=0.
ψ
4i
=0 T
4i
> 0
ψ
4i
=0
ϕ
2i
(P
Ti
)
ϕ
2i
(P
Ti
)=
P
Ti
C
i
+
1
b
4i
C
i
T
4i
(P
0
Ti
− P
Ti
).
ϕ
2i
(P
Ti
)
ϕ
1i
(P
Ti
,q
i
,s
i
)
˙
ψ
3i
(t)=
dq
i
dt
−
∂ϕ
2i
(P
Ti
)
∂P
Ti
dP
Ti
dt
= b
6i
−γ
i
(q
i
) − b
5i
s
i
+ ϕ
1i
(P
Ti
,q
i
,s
i
)
−
−
1
C
i
1 −
1
b
4i
T
4i
b
4i
−P
Ti
+ q
i
C
i
,
ϕ
1i
(P
Ti
,q
i
,s
i
)
ϕ
1i
(P
Ti
,q
i
,s
i
)=γ
i
(q
i
)+b
5i
s
i
+
1
b
6i
C
i
1 −
1
b
4i
T
4i
b
4i
−P
Ti
+ q
i
C
i
−
−
1
b
6i
T
3i
q
i
−
P
Ti
C
i
−
1
b
4i
C
i
T
4i
(P
0
Ti
− P
Ti
)
.
U
2i
U
2i
(s
i
,P
Ti
,q
i
,h
i
)=h
i
+
1
b
7i
∂ϕ
1i
∂P
Ti
dP
Ti
dt
+
∂ϕ
1i
∂s
i
ds
i
dt
+
∂ϕ
1i
∂q
i
dq
i
dt
−
1
T
2i
b
7i
ψ
2i
.
U
2i
P
0
Ti
ω
i
= ω
0
s
i
=0.
P
0
Ti
ψ
4i
=0
P
Ti
= P
0
Ti
.
dδ
i
dt
= s
i
;
ds
i
dt
= b
1i
(P
0
Ti
− E
2
qi
y
ii
sin(α
ii
) − E
qi
E
qj
y
ij
sin(δ
i
− δ
j
− α
ij
) − w
i
);
dw
i
dt
= ξ
i
s
i
.
P
0
Ti
ψ
5i
= ξ
i
s
i
+ β
i
w
i
,
T
5i
˙
ψ
5i
(t)+ψ
5i
=0.
ψ
5i
=0 T
5i
> 0
ψ
5i
= ξ
i
s
i
+ β
i
w
i
=0.
ψ
5i
=0
dδ
i
dt
= s
i
;
dw
i
dt
= −β
i
w
i
.
β
i
> 0
s
i
=0
δ
i
= const
P
0
Ti
˙
ψ
5i
(t)=ξ
i
ds
i
dt
+ β
i
dw
i
dt
= ξ
i
b
1i
P
0
Ti
− E
2
qi
y
ii
sin(α
ii
) − E
qi
E
qj
y
ij
sin(δ
i
− δ
j
− α
ij
) − w
i
+ β
i
ξ
i
s
i
,
P
0
Ti
= P
0
Ti
(δ
i
,δ
j
,s
i
,w
i
)=E
2
qi
(δ
i
)y
ii
sin(α
ii
)+E
qi
(δ
i
)E
qj
(δ
j
)y
ij
sin(δ
i
− δ
j
− α
ij
)−
− w
i
β
i
ξ
i
b
1i
T
5i
− 1
− s
i
β
i
b
1i
+
1
b
1i
T
5i
,
E
qi
(δ
i
) ψ
1i
=0
s
i
=0
P
0
Ti
(δ
i
,δ
j
,s
i
,w
i
)=P
i
(δ
i
,δ
j
) − w
i
β
i
ξ
i
b
1i
T
5i
− 1
,
P
i
(δ
i
,δ
j
) i w
i
T
ki
> 0,k= 1, 5 β
i
> 0.
M
i
(t)
P
Ti
(t) δ
i
(t)
s
i
(t) E
qi
(t) h
i
(t)
U
i
(t)
P
i
(t)
U
1i
(t)
U
2i
(t)
ψ
4i
(t)